Analisis Peran Isteri dalam Mendukung Tugas Pelayanan Penatua di Gereja Protestan Persekutuan Sibaragas Kecamatan Pagaran Kabupaten Tapanuli Utara Tahun 2024 - Fani Ayuni Purba; Iwan Setiawan Tarigan; Rencan C. Marbun; Seri Antonius Tarigan; Ibelala Gea (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This study aims to determine the role of the elderly wife in supporting the husband's ministry duties in the Sibaragas Fellowship Protestant Church. The study used a semi-structured interview method and was analyzed descriptively qualitatively. The results showed that the elderly wife has an important role in providing spiritual and emotional support to her husband, which helps the elderly in dealing with the pressures and challenges of ministry. In addition, the wife's active involvement in ministry has a positive impact on the congregation's view of the husband's leadership. The elderly wife is also expected to be a role model for the congregation and society, not because of coercion, but because of an awareness of her calling. She also plays a role in coordinating women's activities in the church. The lack of wife involvement often causes dissatisfaction with the congregation and can affect the quality of the husband's ministry.